If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-3 + -1x) + -2x = 14 (-3 * 6 + -1x * 6) + -2x = 14 (-18 + -6x) + -2x = 14 Combine like terms: -6x + -2x = -8x -18 + -8x = 14 Solving -18 + -8x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + -8x = 14 + 18 Combine like terms: -18 + 18 = 0 0 + -8x = 14 + 18 -8x = 14 + 18 Combine like terms: 14 + 18 = 32 -8x = 32 Divide each side by '-8'. x = -4 Simplifying x = -4
| I+1=-2 | | 19-x+13=2(x+13) | | 42=8n+13m | | 5x+5y=200 | | -3(4t-3)+7t=2t-2 | | 3x+25=61+3x | | 10=-30-m/5 | | V=(5-3)3 | | 6=w+16 | | (2x+1)-(x-10)=90 | | 7x+21-x=7(x+3) | | -16n-2n=16 | | 14=5-2x | | 2(x-5)-8=6+3(x+2) | | 2B=B-10 | | -2.1=y-4.2 | | 2x+5=14+7/3x | | 7y-5.9=8y | | (-3x^2+5)-(5x^2+2x-6)= | | 8(m-3)=36 | | 2x-5=4(x-3) | | 45=9-8x | | 5m+7m=24 | | 3x+2-7x-5=2x+9 | | 7.72x+16=59.5984+4x | | x^2-5x+19=0 | | 5-5n-4=11 | | r^2=24 | | x+2(5+3x)=87 | | 3x=5-4 | | 3x-5+2x=20 | | 12x+5=4x+3 |